Inspiracje judeohelleńską egzegezą Filona Aleksandryjskiego w pismach św. Hieronima - Mariusz Szram (Vox Patrum, 2012)
Jerome, like most of the early Christian exegetes (Origen, Didymus the Blind, Hilarius of Poitiers, Ambrose, Augustine), respected Philo of Alexandria as a specialist in the field of spiritual exegesis of the Old Testament and called him vir doctissimus Iudaeorum. In his letters and biblical commentaries Jerome used the knowledge on the liturgical vestments of the high priest and their symbolism that can be found in the writings of Philo. However, Jerome probably didn’t use directly his biblical commentaries, but took their content through the works of Origen, in which Philo's ideas have been christianized. The admiration for the person and work of Philo, which can be compared only to that showed in the East by Didymus the Blind, resulted in St. Jerome a certain lack of criticism. In De viris inlustribus Jerome too hastily considered Philo as a thinker deserved for the development of Christianity and attributed to him the works of which he was not the author.